Penerapan Pembelajaran Online Group Whatsapp dalam Masa Pandemi Covid-19 Sebagai Metode Untuk Mencapai Hasil Belajar Siswa - Nur Rohman; Heru Ismaya; Rika Agustiani (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to describe 1). How is the application of whatsapp group online learning in the COVID 19 pandemic?, 2). How is the learning method in the Covid-19 pandemic?, 3). How are the learning outcomes in the Covid-19 pandemic? This study used a qualitative method, the informants of this study were the head of the madrasa, class II-A teacher, and 2 students in class II-A. Collecting data through interviews, observation, and documentation. The data analysis technique used is data reduction, data compilation and categorization. The results of the study: (1) Online learning is carried out online by preparing planning and implementation, the planning includes making materials, assignments and questions. For its implementation, by distributing materials and assignments through whatsapp groups, then for students who do not have mobile phones, the teacher delivers questions at home or parents take them to school. (2) The learning method in online learning is that the teacher makes the material, then the material is photographed and sent via a whatsapp group that is owned by everyone. students then students study it with photo evidence sent back to the whatsapp group as evidence of carrying out learning. Offline is done by students themselves, while online is done every day, assignments are collected according to the agreement with the teacher, namely by photo media and sent via WhatsApp group. The material is adjusted to the basic competencies taken from textbooks and worksheets then the teacher makes questions as a learning evaluation tool. (3) student learning outcomes show that the application of online learning is difficult to achieve student learning outcomes, this is due to several factors, such as rural student houses having difficulty internet signal , many students do not have a whatsapp or mobile phone application, students are less responsible for doing assignments, and the conditions of parents and the environment are not very supportive so that the student learning outcomes achieved are less than optimal.